1520. Determining the Management of Children with Acute UTI/Pyelonephritis Who Do Not Fit Current Management Recommendations. (26th November 2018) - Scanlan, Barry; Ibrahim, Laila; Hopper, Sandy; McNab, Sarah; Babl, Franz; Davidson, Andrew; Bryant, Penelope
Abstract: Background: A 2014 Cochrane review of acute UTI/pyelonephritis in children reported no difference between intravenous (IV) and oral (PO) antibiotics and the AAP recommends the routes as equally efficacious. Despite this, many children continue to be treated with IV antibiotics, with the appropriateness of this unclear. The Cochrane review was based on studies that excluded children with features including vomiting, urological abnormality, previous UTI, or pre-treatment with antibiotics. We aimed to compare: PO vs. IV antibiotics; 1 vs. 2–3 days IV antibiotics; and all patients compared with those in the Cochrane review. Methods: A prospective observational study of children presenting to the ED at a tertiary children's hospital in Australia with UTI/pyelonephritis from May 2016 to November 2017. Data included demographic, clinical features, microbiology, treatment and outcomes. Key features and outcomes were compared. Results: Of 541 children, 378 (70%) received PO antibiotics and 163 (30%) IV/IM. Patients were significantly more likely to receive IV antibiotics if they presented with fever, vomiting, rigors or lethargy, had a history of previous UTI, or were pre-treated with PO antibiotics ( P < 0.05). Of those treated with IV antibiotics, the majority received 1 (38%) or 2 (36%) days prior to PO switch. The only difference in those treated at with 1-day vs. 2–3 days of IV antibiotics was the proportion receiving maintenance IV fluids (table). A substantial number of our patients ( n = 390, 72%) had a urological abnormality, vomiting, previous UTI or were pre-treated with PO antibiotics and therefore the Cochrane recommendations are not applicable. Conclusion: Patients treated with initial IV appear different from those treated with PO antibiotics. However, 1 vs. 2–3 days IV appeared to be similar, suggesting an opportunity for shortening duration. We have provided the first prospective data since the Cochrane review in patients not included in it, showing the gap in evidence. Disclosures: All authors: No reported disclosures.